Analisis Kinerja Karyawan Ditinjau dari Gaya Kepemimpinan, Disiplin Kerja, dan Motivasi Kerja - Prinaldi; Elfiswandi; Ismuhadjar (Jurnal Informatika Ekonomi Bisnis, 2020)
This study aims to find out how much the analysis of employee performance in terms of work discipline, work motivation and leadership style at Kodim 0307 Tanah Datar. Data collection methods through surveys and questionnaires. Total sample of 121 respondents. The analytical method used is regression analysis and correlation analysis. Based on the results of multiple regression analysis, the equation Ŷ = 7.054 + 0.426 X1 + 0.186 X2 + 0.274 X3. There is a positive and significant influence between leadership style (X1) on employee performance (Y), with t count 0.426 or significantly lower than alpha (0.000<0.05). Then a positive and significant effect between work discipline (X2) on employee performance (Y), with a t count of 0.186 or a significant level smaller than alpha (0.012<0.05). There is a positive and significant influence between work motivation (X3) on employee performance (Y), with tcount 0.274 or significantly lower than alpha (0.001>0.05) and significant influence between leadership style (X1), work discipline (X2 ) and work motivation (X3) together on employee performance (Y) as well as a strong relationship between each of these variables with f count 28,534 or a significantly smaller level than alpha (0,000 <0.05).